Lithium ion secondary battery, positive electrode active material, preparation method of positive electrode active material and electric equipment

By using nickel-cobalt-manganese oxides and specific distribution of secondary particles in the positive electrode sheet of lithium-ion secondary battery, the problem of low compaction density of the positive electrode sheet is solved, and the volume energy density and electrochemical performance of the battery are improved.

CN119833709AActive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411729779.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-15
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The low compaction density of the positive electrode sheet in lithium-ion secondary batteries is caused by low battery volume energy density.

Method used

Nickel-cobalt-manganese oxide is used as the positive electrode active material. The molar content of nickel element in the transition metal element is greater than or equal to 0.85, and a polycrystalline material structure is formed to improve compaction density through specific secondary particle size and quantity distribution.

Benefits of technology

The volume energy density of lithium-ion secondary batteries is improved and the electrochemical performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833709A_ABST
    Figure CN119833709A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion secondary battery, a positive electrode active material, a preparation method and electric equipment, the lithium ion secondary battery comprises a positive electrode plate, a negative electrode plate and an electrolyte, the positive electrode plate comprises the positive electrode active material, the positive electrode active material comprises secondary particles, and the secondary particles are arranged in the negative electrode plate. The secondary particles comprise a first type of secondary particles, a second type of secondary particles and a third type of secondary particles, and the volume particle size distribution of the first type of secondary particles is 3 [mu] mlt; d11 < = 7.5 [mu] m; the volume particle size distribution of the second type of secondary particles is 7.5 [mu] mlt; d12 < = 11 [mu] m; the volume particle size distribution of the third secondary particles is 11 [mu] mlt; d13 < = 15 [mu] m; based on the total number of the secondary particles, the number proportion of the first type of secondary particles is 2% < = N1lt; the number ratio of the second type of secondary particles is 70% < = N2lt; the number ratio of the third secondary particles is 5% < = N3lt; and 28%. By utilizing the secondary particles with the ratio, the compaction density of the positive pole piece is improved, and the volume energy density of the lithium ion secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of lithium batteries, and in particular to lithium ion secondary batteries, cathode active materials and their preparation methods, and electrical equipment. Background Art

[0002] In recent years, lithium ion batteries have achieved great development. Lithium ion batteries can be widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in many fields such as electric vehicles, electric tools, military equipment, and aerospace. Among them, when lithium ion batteries are applied to electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as the market's demand for the battery life of electric vehicles is getting higher and higher, how to improve the volumetric energy density of the battery needs to be further solved. The above statements are only used to provide background technical information related to this application, and do not necessarily constitute prior art. Summary of the Invention

[0003] In view of this, this application provides a lithium ion secondary battery, a cathode active material and its preparation method, and electrical equipment to solve the technical problem of low volumetric energy density of the battery caused by the low compaction density of the cathode electrode in the lithium ion secondary battery.

[0004] In the first aspect of this application, a lithium ion secondary battery is provided. The lithium ion secondary battery includes a cathode electrode, an anode electrode, and an electrolyte. The cathode electrode includes a cathode active material. The cathode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85. The cathode active material includes secondary particles. The secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm. The secondary particles include a first type of secondary particles, a second type of secondary particles, and a third type of secondary particles. The volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm. Based on the total number of secondary particles, the number proportion of the first type of secondary particles is N1, 2% ≤ N1 < 10%. The volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm. Based on the total number of secondary particles, the number proportion of the second type of secondary particles is N2, 70% ≤ N2 < 85%. The volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm. Based on the total number of secondary particles, the number proportion of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

[0005] In this embodiment, the molar content of nickel in all transition metal elements is greater than or equal to 0.85, and the specific capacity of the positive electrode active material is relatively high, so that the energy density of the lithium-ion secondary battery is relatively high. The secondary particles include primary particles, and the average particle size of the primary particles is 50nm to 2μm. The positive electrode active material provided in the present application is a polycrystalline material, and the polycrystalline material is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected by grain boundaries. Further, the secondary particles include a first secondary particle, a second secondary particle, and a third secondary particle. The particle size and number distribution of the secondary particles are within the above range, which can increase the compaction density of the positive electrode sheet, and the particle size and number distribution of the secondary particles make it difficult for the secondary particles to break as the compaction density of the positive electrode sheet increases, so that the lithium-ion secondary battery has a higher volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0006] In one embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the round secondary particles are secondary particles in which, in a scanning electron microscope image, the ratio of the longest diameter to the shortest diameter is d1 / d2, and 1≤d1 / d2≤1.2.

[0007] In the present embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the ratio of their longest diameter to their shortest diameter is within the above range, so that the internal arrangement of the secondary particles is more orderly, the friction between the secondary particles is reduced, and the compaction density is greater under the same pressure; during the cyclic charge and discharge process, the degree of stress accumulation inside the round secondary particles is lower, and the generated stress is easier to release, reducing the probability of secondary particle breakage, so that the lithium-ion secondary battery has a higher volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0008] In one embodiment, the ratio of the number of the second secondary particles to the number of the first secondary particles is 7 to 42.5.

[0009] In this embodiment, the ratio of the number of the second secondary particles to the number of the first secondary particles is within the above range, which can increase the compaction density of the positive electrode sheet, and the number distribution of this type of secondary particles makes it difficult for the secondary particles to break as the compaction density of the positive electrode sheet increases, thereby enabling the lithium-ion secondary battery to have a higher volume energy density and improving the electrochemical performance of the lithium-ion secondary battery.

[0010] In one embodiment, the average particle size of the primary particles is 100 nm to 500 nm.

[0011] In this embodiment, the average particle size of the primary particles is within the above range, so that the primary particles have a shorter electron transmission path, which helps to improve the electron transmission efficiency, thereby improving the charge and discharge performance of the battery, and can make the electrochemical performance of the lithium-ion secondary battery better.

[0012] In one embodiment, the compaction density of the positive electrode active material at a pressure of 5T is 3.35 g / cm 3 ~3.6g / cm 3 .

[0013] In the present embodiment, the compaction density of the positive electrode active material is within the above range, and the lithium ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0014] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.35 m 2 / g~0.75m 2 / g.

[0015] In the present embodiment, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the volume energy density of the lithium ion secondary battery is better.

[0016] In one embodiment, the gram weight is 1.4×10 -4 g / mm 2 ~2.3×10 -4 g / mm 2 The compaction density of the positive electrode sheet at 0.7% extension is 3.35 g / cm 3 ~3.7g / cm 3 .

[0017] In this embodiment, the compaction density of the positive electrode sheet is within the above range, and the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery. -4 g / mm 2 ~2.3×10 -4 g / mm 2 The preferred compaction density of the positive electrode sheet at 0.7% extension is 3.4 g / cm 3 ~3.65g / cm 3 .

[0018] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O nMaterials; 0.5 ≤ a ≤ 1.2, 0.85 ≤ b ≤ 0.99, 0 < c ≤ 0.1, 0 < d ≤ 0.05, 1.9 ≤ n ≤ 2.2, M1 includes one or a combination of more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, Ti.

[0019] In this embodiment, the cathode active material combines the advantages of the three elements of nickel, cobalt, and manganese. At the same time, the doping element M1 helps to improve the bulk phase stability and electrical stability of the cathode active material, reduce the cation mixing problem caused by high nickel, and is also beneficial to promoting the growth of radial primary particles, thereby improving the electrochemical performance of the cathode active material.

[0020] The second aspect of the present application also provides a method for preparing a lithium-ion secondary battery, including: providing a slurry containing a cathode active material, coating the slurry containing the cathode active material on a cathode current collector to form a cathode electrode sheet, the cathode active material including lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements being greater than or equal to 0.85; the cathode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include a first type of secondary particle, a second type of secondary particle, and a third type of secondary particle, the volume particle size distribution of the first type of secondary particle being d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the proportion of the number of the first type of secondary particle is N1, 2% ≤ N1 < 10%; the volume particle size distribution of the second type of secondary particle is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the proportion of the number of the second type of secondary particle is N2, 70% ≤ N2 < 85%; the volume particle size distribution of the third type of secondary particle is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the proportion of the number of the third type of secondary particle is N3, 5% ≤ N3 < 28%; arranging a separator between the cathode electrode sheet and the anode electrode sheet to form a lithium-ion secondary battery.

[0021] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor in all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. The secondary particles include primary particles, the average particle size of the primary particles is 50nm to 2μm, and the positive electrode active material provided in the present application is a polycrystalline material, which is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected by grain boundaries. The positive electrode active material includes secondary particles, and the secondary particles include a first secondary particle, a second secondary particle, and a third secondary particle, which is prepared once. The lithium-ion secondary battery prepared by the above method has a high compaction density of the positive electrode sheet, and the secondary particles in the positive electrode sheet are not easy to break as the compaction density of the positive electrode sheet increases, so that the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0022] In one embodiment, the preparation method of the positive electrode active material includes: providing a solution containing a nickel source, a cobalt source and a manganese source, wherein the molar ratio of the nickel source, the cobalt source and the manganese source is x:y:(1-xy), x≥0.85; adding a complexing agent with a concentration of 0.2mol / L to 3.5mol / L and a precipitating agent with a concentration of 0.3mol / L to 0.5mol / L to the solution containing the nickel source, the cobalt source and the manganese source, and controlling the pH range to 12.1 to 13 under an inert atmosphere, and heating at 50°C to Under 70°C, the reaction is carried out for 4h to 7h to form a first intermediate product; the pH of the first intermediate product is adjusted to 10.5 to 11, and the reaction is carried out for 13h to 17h to obtain a second intermediate product; the pH of the second intermediate product is adjusted to 10 to 10.4, and the reaction is carried out for 55h to 80h to obtain nickel cobalt manganese hydroxide, and the volume average particle size DV50 of the nickel cobalt manganese hydroxide is 8.5μm to 12μm; the nickel cobalt manganese hydroxide is mixed with a lithium salt, and a lithium nickel cobalt manganese oxide positive electrode material is obtained after sintering.

[0023] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor to all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. In the preparation process of the nickel-cobalt-manganese hydroxide precursor, the precipitant reacts with the nickel source, the cobalt source and the manganese source to generate a precipitate, and the complexing agent can effectively complex metal ions such as Ni, Co, and Mn in the liquid, which helps to control the composition of the positive active material precursor. The concentration of the mixed salt solution, the concentration of the precipitant, the concentration of the complexing agent, the pH, the temperature and the time are controlled within the above range, so that the nickel-cobalt-manganese hydroxide precursor has the particle size distribution of the secondary particles provided in the first aspect of the present application. Specifically, in the first intermediate product stage, the pH is controlled in the range of 12.1 to 13. Maintaining a higher pH can inhibit the seed growth of the overall particles and maintain the uniform size of the secondary particles. The number of seeds is adjusted by controlling the nucleation time to 4h to 7h; in the second intermediate product stage, the pH of the reaction is reduced and adjusted to 10.5 to 11, so that the reaction transitions from nucleation to growth. Reducing the pH in a short time can reduce the generation of new nuclei and improve the consistency of the particle size of the secondary particles; the nickel cobalt manganese hydroxide stage is the growth period, and maintaining a low pH in the range of 10 to 10.4 can inhibit nucleation and reduce the probability of small particles. Stable reaction conditions can improve the crystallinity of the overall secondary particles. Further, the volume average particle size DV50 of the nickel cobalt manganese hydroxide precursor can be controlled within the range of 8.5μm to 12μm, which helps to further control the volume average particle size DV50 of the lithium nickel cobalt manganese oxide positive electrode material.

[0024] In one embodiment, nickel cobalt manganese hydroxide is mixed with a lithium salt and sintered to obtain a lithium nickel cobalt manganese oxide positive electrode material, including: mixing nickel cobalt manganese hydroxide with a lithium salt and sintering for a first time to obtain a first product; mixing the first product with a first coating source and sintering for a second time to obtain a second product, wherein the temperature of the second sintering is lower than the temperature of the first sintering.

[0025] In this embodiment, nickel cobalt manganese hydroxide is mixed with lithium salt, and after the first high-temperature sintering, a first product is obtained; the first product is mixed with the first coating source, and after the second sintering, a second product is obtained, and the second product is a lithium nickel cobalt manganese oxide positive electrode material with the first coating source coated on the surface. After the secondary sintering, the material has a better crystallization state, thereby improving the electrochemical performance of the lithium nickel cobalt manganese oxide positive electrode material. The coating layer formed by the first coating source can also reduce the possibility of side reactions between the lithium nickel cobalt manganese oxide positive electrode material and the electrolyte, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0026] In one embodiment, the first sintering temperature is 725° C. to 780° C., and the first sintering time is 7 h to 14 h; or / and, the second sintering temperature is 400° C. to 615° C., and the second sintering time is 5 h to 11 h.

[0027] In this embodiment, the first sintering temperature and time, and the second sintering temperature and time are controlled within the above ranges, respectively, so that the material has a better crystal state, thereby improving the electrochemical performance of the lithium nickel cobalt manganese oxide positive electrode material.

[0028] In one embodiment, nickel cobalt manganese hydroxide is mixed with a lithium salt and subjected to a first sintering to obtain a first product, comprising: mixing nickel cobalt manganese hydroxide, a lithium salt and a doping source and subjected to a first sintering to obtain a first product, wherein the doping source comprises one or more of a Mg source, a Na source, a Zr source, a Y source, an Al source, a Ca source, a W source, a Nb source, a Ta source, a Sr source or a Ti source.

[0029] In this embodiment, one or more of Mg source, Na source, Zr source, Y source, Al source, Ca source, W source, Nb source, Ta source, Sr source or Ti source are added to the positive electrode active material to improve the crystal structure of the material and reduce the distortion of the layered structure, thereby improving the structural stability and cycle life of the lithium nickel cobalt manganese oxide positive electrode material.

[0030] In one embodiment, the first coating source includes one or more of a Co source, an Al source, a F source, and a Ti source.

[0031] In this embodiment, the first coating source is conducive to improving the structural stability of the positive electrode active material, thereby improving the electrochemical performance of the positive electrode active material. The use of the Co source for coating is mainly to reduce the residual alkali on the surface of the positive electrode active material. The residual alkali will produce a large amount of gas at high pressure and will also aggravate the side reactions between the positive electrode active material and the electrolyte. Therefore, the reduction of the residual alkali can improve the stability of the lithium-ion secondary battery. The coating layer formed by the Al source can delay the erosion of the electrolyte and reduce the generation of by-products; the main function of the F source is to form a quasi-artificial solid electrolyte interface film (CEI film) on the surface of the positive electrode active material. The quasi-artificial CEI film formed by AlF3 can effectively reduce the erosion of the electrolyte and improve the interface stability. The main function of the F source is to form a quasi-artificial CEI film. The quasi-artificial CEI film formed by AlF3 can effectively reduce the erosion of the electrolyte and improve the interface stability; the coating layer formed by the Ti source can enhance the strength of the positive electrode active material.

[0032] In one embodiment, after the first product is mixed with the first coating source and subjected to a second sintering to obtain the second product, the method further includes: mixing the second product with the second coating source and subjected to a third sintering to obtain a third product, wherein the third product is a lithium nickel cobalt manganese oxide positive electrode material.

[0033] In one embodiment, the temperature of the third sintering is 250°C to 348°C, and the time of the third sintering is 5 h to 12 h; the second coating source includes one or more of the first types among the B source, the Al source, and the Y source.

[0034] In this embodiment, after mixing the first product with the first coating source and performing the second sintering to obtain a lithium nickel cobalt manganese oxide cathode material with the first coating source coated on the surface, the lithium nickel cobalt manganese oxide cathode material is mixed with the second coating source and subjected to the third sintering. The second coating source is coated outside the first coating source to obtain a double-coated lithium nickel cobalt manganese oxide cathode material. The second coating source is beneficial to improving the interfacial stability of the cathode active material and improving the lithium ion insertion / extraction ability. Among them, the B source can refine the primary grains and improve the lithium ion insertion / extraction ability on the surface. The coating formed by the Y source is easy to form a protective layer on the surface, reduce the surface activity, and enhance the interfacial stability; the AlF3 forms an artificial CEI-like film that can effectively help reduce the erosion of the electrolyte and improve the interfacial stability.

[0035] The third aspect of the present application further provides a cathode active material, including lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the cathode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include: the first type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particles is N1, 2% ≤ N1 < 10%; the second type of secondary particles, the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particles is N2, 70% ≤ N2 < 85%; the third type of secondary particles, the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the number proportion of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

[0036] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor in all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. The secondary particles include primary particles, the average particle size of the primary particles is 50nm to 2μm, and the positive electrode active material provided in the present application is a polycrystalline material, which is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected by grain boundaries. The positive electrode active material includes secondary particles, and the secondary particles include a first secondary particle, a second secondary particle, and a third secondary particle, and the secondary particles are prepared once. The lithium-ion secondary battery prepared by the above method has a high compaction density of the positive electrode sheet, and the secondary particles in the positive electrode sheet are not easy to break as the compaction density of the positive electrode sheet increases, so that the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0037] In one embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the round secondary particles are secondary particles in which, in a scanning electron microscope image, the ratio of the volume particle size distribution to the shortest diameter is d1 / d2, and 1≤d1 / d2≤1.2.

[0038] In the present embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the ratio of their longest diameter to their shortest diameter is within the above range, so that the internal arrangement of the secondary particles is more ordered, the friction between the secondary particles is reduced, and under the same pressure conditions, the compaction density is greater; during the cyclic charge and discharge process, the degree of stress accumulation inside the round secondary particles is lower, and the generated stress is easier to release, reducing the probability of secondary particle breakage, so that the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0039] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O n material; 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤n≤2.2, M1 includes a combination of one or more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, and Ti.

[0040] In this embodiment, the positive electrode active material combines the advantages of nickel, cobalt, and manganese. At the same time, the doping element M1 helps to improve the bulk phase stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and is also beneficial to promoting the growth of radial primary particles, thereby improving the electrochemical performance of the positive electrode active material.

[0041] The fourth aspect of the present application further provides a method for preparing a positive electrode active material, including: providing a solution containing a nickel source, a cobalt source, and a manganese source, wherein the molar ratio of the nickel source, the cobalt source, and the manganese source is x:y:(1 - x - y), and x ≥ 0.85; adding a complexing agent with a concentration of 0.2 mol / L to 3.5 mol / L and a precipitating agent with a concentration of 0.3 mol / L to 0.5 mol / L into the solution containing the nickel source, the cobalt source, and the manganese source, under an inert atmosphere, controlling the pH range to be 12.1 to 13, and reacting at 50 to 70 °C for 4 h to 7 h to form a first intermediate product; adjusting the pH of the first intermediate product to 10.5 to 11 and reacting for 13 h to 17 h to obtain a second intermediate product; adjusting the pH of the second intermediate product to 10 to 10.4 and reacting for 55 h to 80 h to obtain nickel cobalt manganese hydroxide, and the volume average particle size DV50 of the nickel cobalt manganese hydroxide is 8.5 μm to 12 μm; mixing the nickel cobalt manganese hydroxide with a lithium salt and sintering to obtain a lithium nickel cobalt manganese oxide positive electrode material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include a first type of secondary particle, a second type of secondary particle, and a third type of secondary particle, the volume particle size distribution of the first type of secondary particle is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particle is N1, 2% ≤ N1 < 10%; the volume particle size distribution of the second type of secondary particle is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the number proportion of the second type of secondary particle is N2, 70% ≤ N2 < 85%; the volume particle size distribution of the third type of secondary particle is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the number proportion of the third type of secondary particle is N3, 5% ≤ N3 < 28%.

[0042] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor to all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. In the preparation process of the nickel-cobalt-manganese hydroxide precursor, the precipitant reacts with the nickel source, the cobalt source and the manganese source to generate a precipitate, and the complexing agent can effectively complex metal ions such as Ni, Co, and Mn in the liquid, which helps to control the composition of the positive active material precursor. The concentration of the mixed salt solution, the concentration of the precipitant, the concentration of the complexing agent, the pH, the temperature and the time are controlled within the above range, so that the nickel-cobalt-manganese hydroxide precursor has the particle size distribution of the secondary particles provided in the first aspect of the present application. Specifically, in the stage of forming the first intermediate product, the pH is controlled in the range of 12.1 to 13. Maintaining a relatively high pH can inhibit the seed growth of the overall particles and maintain the uniform particle size of the secondary particles. The number of seeds is adjusted by controlling the nucleation time to 4h to 7h. In the stage of forming the second intermediate product, the pH of the reaction is lowered and adjusted to 10.5 to 11, so that the reaction transitions from nucleation to growth. Lowering the pH in a short time can reduce the generation of new nuclei and improve the consistency of the particle size of the secondary particles. The stage of forming nickel cobalt manganese hydroxide is the growth period. Maintaining a low pH in the range of 10 to 10.4 can inhibit nucleation and reduce the probability of small particles. Stable reaction conditions can improve the crystallinity of the overall secondary particles.

[0043] In one embodiment, nickel cobalt manganese hydroxide is mixed with a lithium salt and sintered to obtain a lithium nickel cobalt manganese oxide positive electrode material, including: mixing nickel cobalt manganese hydroxide with a lithium salt, sintering for the first time to obtain a first product, the temperature of the first sintering is 725°C to 780°C, and the time of the first sintering is 7h to 14h; mixing the first product with a first coating source, sintering for a second time to obtain a second product; the temperature of the second sintering is 400°C to 615°C, the time of the second sintering is 5h to 11h, and the first coating source includes one or more of a Co source, an Al source, a F source, and a Ti source; mixing the second product with a second coating source, sintering for a third time to obtain a third product, the third product is a lithium nickel cobalt manganese oxide positive electrode material, the temperature of the third sintering is 250°C to 348°C, and the time of the third sintering is 5h to 12h; the second coating source includes the first or more of a B source, an Al source, and a Y source.

[0044] In this embodiment, nickel cobalt manganese hydroxide is mixed with lithium salt, and a first product is obtained after a first high-temperature sintering; the first product is mixed with a first coating source, and a second product is obtained after a second sintering, and the second product is a lithium nickel cobalt manganese oxide positive electrode material whose surface is coated with the first coating source. After the second sintering, the material has a better crystallization state, thereby improving the electrochemical performance of the lithium nickel cobalt manganese oxide positive electrode material. The coating layer formed by the first coating source can also reduce the possibility of side reactions between the lithium nickel cobalt manganese oxide positive electrode material and the electrolyte, thereby improving the electrochemical performance of the lithium ion secondary battery. The first sintering temperature and time, the second sintering temperature and time are controlled within the above range respectively, so that the material has a better crystallization state, thereby improving the electrochemical performance of the lithium nickel cobalt manganese oxide positive electrode material. The first product is mixed with the first coating source, and after the second sintering, a lithium nickel cobalt manganese oxide positive electrode material with the first coating source coated on the surface is obtained. Then, the lithium nickel cobalt manganese oxide positive electrode material is mixed with the second coating source, and after the third sintering, the second coating source is coated on the outside of the first coating source to obtain a two-layer coated lithium nickel cobalt manganese oxide positive electrode material. The second coating source is beneficial to improve the interface stability of the positive electrode active material and improve the deintercalation ability of lithium ions. Among them, the B source will be converted into lithium boron oxide, which can be used as a fast ion conductor, thereby improving the electrochemical performance of lithium-ion secondary batteries.

[0045] In one embodiment, nickel cobalt manganese hydroxide is mixed with a lithium salt and sintered to obtain a lithium nickel cobalt manganese oxide positive electrode material, including: mixing nickel cobalt manganese hydroxide, a lithium salt and a doping source, and sintering for the first time to obtain a first product, wherein the doping source includes one or more of a Mg source, a Na source, a Zr source, a Y source, an Al source, a Ca source, a W source, a Nb source, a Ta source, a Sr source or a Ti source.

[0046] In this embodiment, one or more of Mg source, Na source, Zr source, Y source, Al source, Ca source, W source, Nb source, Ta source, Sr source or Ti source are added to the positive electrode active material to improve the crystal structure of the material and reduce the distortion of the layered structure, thereby improving the structural stability and cycle life of the lithium nickel cobalt manganese oxide positive electrode material.

[0047] The fifth aspect of the present application provides an electrical device, including any of the above lithium-ion secondary batteries, or / and, a lithium-ion secondary battery prepared by any of the above preparation methods, or / and any of the above positive electrode active materials, or / and, a positive electrode active material prepared by any of the above methods for preparing positive electrode active materials. The electrical device of the embodiment of the present application has at least the same advantages as the lithium-ion secondary battery of the first aspect, or / and at least the same advantages as the lithium-ion secondary battery prepared by the method for preparing the lithium-ion secondary battery of the second aspect, or / and at least the same advantages as the positive electrode active material of the third aspect, or / and at least the same advantages as the positive electrode active material prepared by the method for preparing the positive electrode active material of the fourth aspect.

[0048] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is a scanning electron microscope image of secondary particles according to one embodiment of the present application;

[0050] Figure 2 is a particle size distribution diagram of secondary particles according to one embodiment of the present application;

[0051] Figure 3 It is a schematic flow chart of a method for preparing a positive electrode active material according to an embodiment of the present application;

[0052] Figure 4 is a schematic flow chart of a method for preparing a positive electrode active material according to another embodiment of the present application;

[0053] Figure 5 It is a schematic flow chart of a method for preparing a positive electrode active material according to another embodiment of the present application;

[0054] Figure 6 It is a schematic structural diagram of a battery cell according to one embodiment of the present application.

[0055] Figure 7 It is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application.

[0056] Figure 8a It is a schematic diagram of the partial structure of an electrical equipment according to one embodiment of the present application.

[0057] Figure 8b It is a schematic diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0058] Below, the battery cells, batteries and electrical equipment of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0059] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0060] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0061] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0062] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0063] Unless otherwise specified, the terms "comprising" and "including" mentioned in this application are open-ended and can also be closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included or comprised, or it can mean that only the listed components are included or comprised.

[0064] Unless otherwise specified, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0065] During the production of the positive electrode sheet, in order to increase the compaction density of the positive electrode sheet, the compaction density can be increased by increasing the cold pressing pressure. However, as the cold pressing pressure increases, the secondary particles of the positive active material are prone to breakage, reducing the electrochemical performance of the lithium-ion secondary battery.

[0066] Based on this, a first aspect of this application provides a lithium-ion secondary battery. The lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. The positive electrode sheet includes a positive active material. The positive active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the positive active material includes secondary particles. Refer to Figure 1 , the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; refer to Figure 2 , the secondary particles include a first type of secondary particle, a second type of secondary particle, and a third type of secondary particle. The volume particle size distribution of the first type of secondary particle is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particle is N1, 2% ≤ N1 < 10%; the volume particle size distribution of the second type of secondary particle is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the number proportion of the second type of secondary particle is N2, 70% ≤ N2 < 85%; the volume particle size distribution of the third type of secondary particle is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the number proportion of the third type of secondary particle is N3, 5% ≤ N3 < 28%.

[0067] In this embodiment, the molar content of nickel in all transition metal elements is greater than or equal to 0.85, and the specific capacity of the positive electrode active material is relatively high, so that the energy density of the lithium-ion secondary battery is relatively high. The secondary particles include primary particles, and the average particle size of the primary particles is 50nm to 2μm. The positive electrode active material provided in the present application is a polycrystalline material, and the polycrystalline material is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected by grain boundaries. Further, the secondary particles include a first secondary particle, a second secondary particle, and a third secondary particle. The particle size and number distribution of the secondary particles are within the above range, which can increase the compaction density of the positive electrode sheet, and the particle size and number distribution of the secondary particles make it difficult for the secondary particles to break as the compaction density of the positive electrode sheet increases, so that the lithium-ion secondary battery has a higher volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0068] Among them, the average particle size of the primary particles can be 50nm, 85nm, 100nm, 180nm, 220nm, 300nm, 500nm, 1μm, 1.5μm, 1.7μm, 2μm, etc., or a range consisting of any two of the above values, for example, 50nm~1μm, 1μm~1.5μm, 1.5μm~2μm, 100nm~500nm, 300nm~1.7μm, etc.

[0069] The volume particle size distribution d11 of the first secondary particles can be 3.1μm, 3.5μm, 3.7μm, 4μm, 4.5μm, 5.5μm, 6μm, 6.7μm, 7.5μm, etc., or a range formed by any two of the above values, for example, 3.1μm~3.7μm, 3.7μm~7.5μm, 3.5μm~5.5μm, 4.5μm~6.7μm, 5.5μm~7.5μm, etc. Based on the total number of secondary particles, the number percentage N1 of the first type of secondary particles can be 2%, 2.2%, 2.5%, 3.5%, 4%, 4.5%, 5%, 5.2%, 6.7%, 7%, 8%, 9.5%, 9.99%, etc., or a range formed by any two of the above values, for example, 2% to 5.2%, 5.2% to 9.99%, 4.5% to 7%, 3.5% to 9.5%, etc.

[0070] The volume particle size distribution d12 of the second secondary particles can be 7.55μm, 7.85μm, 8.5μm, 9μm, 9.8μm, 10μm, 10.5μm, 11μm, etc., or a range consisting of any two of the above values, such as 7.55μm-9.8μm, 9.8μm-11μm, 8.5μm-10μm, 7.85μm-9μm, 9μm-10.5μm, etc. Based on the total number of secondary particles, the number proportion N2 of the second secondary particles can be 70%, 72%, 75%, 78%, 80%, 81%, 82%, 83.5%, 84%, 84.9%, etc., or a range consisting of any two of the above values, such as 70%-78%, 78%-81%, 81%-84.9%, etc.

[0071] The volume particle size distribution d13 of the third secondary particles can be 11.1 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 14 μm, 14.5 μm, 15 μm, etc., or a range consisting of any two of the above values, such as 11.1 μm to 12.5 μm, 12.5 μm to 14 μm, 14 μm to 15 μm, etc. Based on the total number of secondary particles, the number proportion N3 of the third secondary particles can be 5%, 8%, 8.5%, 10%, 15%, 17.5%, 20%, 23%, 25%, 27.9%, etc., or a range consisting of any two of the above values, such as 5% to 8.5%, 8.5% to 17.5%, 17.5% to 27.9%, etc.

[0072] The average particle size of the primary particles is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0073] The volume particle size distribution is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0074] In one embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the round secondary particles are secondary particles in which, in a scanning electron microscope image, the ratio of the longest diameter to the shortest diameter is d1 / d2, and 1≤d1 / d2≤1.2.

[0075] In the present embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the ratio of their longest diameter to their shortest diameter is within the above range, so that the internal arrangement of the secondary particles is more orderly, the friction between the secondary particles is reduced, and under the same pressure conditions, the compaction density is greater; during the cyclic charge and discharge process, the degree of stress accumulation inside the round secondary particles is lower, and the generated stress is easier to release, reducing the probability of secondary particle breakage, so that the lithium-ion secondary battery has a higher volume energy density, and the electrochemical performance of the lithium-ion secondary battery is improved.

[0076] The ratio d1 / d2 of the longest diameter to the shortest diameter of the secondary particles can be 1, 1.05, 1.1, 1.12, 1.15, 1.18, 1.2, etc., or a range consisting of any two of the above values, such as 1-1.1, 1.1-1.2, 1.12-1.18, etc.

[0077] In one embodiment, the ratio of the number of the second secondary particles to the number of the first secondary particles is 7 to 42.5.

[0078] In this embodiment, the ratio of the number of the second secondary particles to the number of the first secondary particles is within the above range, which can increase the compaction density of the positive electrode sheet, and the number distribution of this type of secondary particles makes it difficult for the secondary particles to break as the compaction density of the positive electrode sheet increases, thereby enabling the lithium-ion secondary battery to have a higher volume energy density and improving the electrochemical performance of the lithium-ion secondary battery.

[0079] The ratio of the number of the second secondary particles to the number of the first secondary particles can be 7, 9, 10, 15, 18.5, 22, 26, 31, 35, 39, 42.5, etc., or a range consisting of any two of the above values, for example, 7-15, 15-26, 26-35, 35-42.5, 10-31, 18.5-39, etc.

[0080] In one embodiment, the average particle size of the primary particles is 100 nm to 500 nm.

[0081] In this embodiment, the average particle size of the primary particles is within the above range, so that the primary particles have a shorter electron transmission path, which helps to improve the electron transmission efficiency, thereby improving the charge and discharge performance of the battery, and can make the electrochemical performance of the lithium-ion secondary battery better.

[0082] The average particle size of the primary particles can be 100nm, 155nm, 190nm, 220nm, 290nm, 350nm, 400nm, 420nm, 460nm, 485nm, 500nm, etc., or a range consisting of any two of the above values, for example, 100nm~290nm, 290nm~420nm, 420nm~500nm, 155nm~350nm, 190nm~400nm, 220nm~485nm, etc.

[0083] In one embodiment, the compaction density of the positive electrode active material at a pressure of 5T is 3.35 g / cm 3 ~3.6g / cm 3 .

[0084] The compacted density is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0085] In the present embodiment, the compaction density of the positive electrode active material is within the above range, and the lithium ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0086] The compacted density of the positive electrode active material can be 3.35 g / cm 3 、3.38g / cm 3 , 3.40g / cm 3 、3.45g / cm 3 、3.50g / cm 3 、3.52g / cm 3 、3.56g / cm 3 、3.58g / cm 3 、3.6g / cm 3 etc., or a range consisting of any two of the above values, such as 3.35 g / cm 3 ~3.45g / cm 3 、3.45g / cm 3 ~3.52g / cm 3 、3.52g / cm 3 ~3.6g / cm 3 , 3.40g / cm 3 ~3.58g / cm 3 、3.45g / cm 3 ~3.6g / cm 3 wait.

[0087] In one embodiment, the specific surface area of ​​the positive electrode active material is 0.35 m 2 / g~0.75m 2 / g.

[0088] In the present embodiment, the specific surface area of ​​the positive electrode active material is within the above range, so that the compaction density of the positive electrode active material is better, and the volume energy density of the lithium ion secondary battery is better.

[0089] The specific surface area is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0090] The specific surface area of ​​the positive electrode active material can be 0.35m 2 / g, 0.38m 2 / g, 0.45m 2 / g, 0.52m 2 / g, 0.58m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g, etc., or a range consisting of any two of the above values, such as 0.35m 2 / g~0.58m 2 / g, 0.58m 2 / g~0.65m 2 / g, 0.65m 2 / g~0.75m 2 / g, 0.52m 2 / g~0.7m 2 / g, etc.

[0091] In one embodiment, the gram weight is 1.4×10 -4 g / mm 2 ~2.3×10 -4 g / mm 2 The compaction density of the positive electrode sheet at 0.7% extension is 3.35 g / cm 3 ~3.7g / cm 3 .

[0092] In this embodiment, the compaction density of the positive electrode sheet is within the above range, and the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery. -4 g / mm 2 ~2.3×10 -4 g / mm 2 The preferred compaction density of the positive electrode sheet at 0.7% extension is 3.4 g / cm 3 ~3.65g / cm 3 .

[0093] The compaction density of the positive electrode can be 3.35g / cm 3 、3.39g / cm 3 , 3.4g / cm3, 3.42g / cm 3 、3.46g / cm 3 、3.50g / cm 3 、3.52g / cm 3 、3.57g / cm 3 、3.59g / cm 3 、3.6g / cm 3 , 3.65g / cm3, 3.66g / cm 3 、3.7g / cm 3 etc., or a range consisting of any two of the above values, such as 3.35 g / cm 3 ~3.46g / cm 3 、3.46g / cm 3 ~3.52g / cm 3 、3.52g / cm 3 ~3.7g / cm 3 、3.4g / cm 3 ~3.57g / cm 3 、3.57g / cm 3 ~3.65g / cm 3 wait.

[0094] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O n material; 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤n≤2.2, M1 includes a combination of one or more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, and Ti.

[0095] In this embodiment, the positive electrode active material combines the advantages of the three elements of nickel, cobalt and manganese. At the same time, the doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and promote the growth of radial primary particles, thereby improving the electrochemical properties of the positive electrode active material.

[0096] In the embodiments of the present application, the substances for providing the M1 source include, but are not limited to, sodium carbonate, sodium hydroxide, zirconium hydroxide, zirconium oxide, zirconium carbonate, magnesium oxide, magnesium hydroxide, magnesium carbonate, titanium oxide, titanium hydroxide, titanium carbonate, tungsten oxide, tungsten hydroxide, tungsten carbonate, niobium oxide, niobium hydroxide, niobium carbonate, tantalum hydroxide, tantalum carbonate, strontium hydroxide, strontium oxide, strontium carbonate, strontium phosphate, calcium hydroxide, calcium oxide, calcium carbonate, calcium phosphate, aluminum oxide, aluminum hydroxide, yttrium oxide, yttrium hydroxide, etc.

[0097] In some embodiments, the positive electrode active material further includes a coating layer, and the coating layer includes elements such as Al, B, Co, Y, etc. The coating layer including Co element can reduce the residual alkali formed during the manufacturing process. The coating layer including B element can refine the crystal grains, which is beneficial to the insertion and extraction of active particles. The coating layer including Al element or Y element can improve the interface stability of the positive electrode active material.

[0098] The second aspect of the present application also provides a method for preparing a lithium-ion secondary battery, including: providing a slurry containing a positive electrode active material, coating the slurry containing the positive electrode active material on a positive electrode current collector to form a positive electrode plate, where the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include a first type of secondary particles, a second type of secondary particles, and a third type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particles is N1, 2% ≤ N1 < 10%; the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the number proportion of the second type of secondary particles is N2, 70% ≤ N2 < 85%; the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the number proportion of the third type of secondary particles is N3, 5% ≤ N3 < 28%; arranging a separator between the positive electrode plate and the negative electrode plate to form a lithium-ion secondary battery.

[0099] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor in all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. The secondary particles include primary particles, the average particle size of the primary particles is 50nm to 2μm, and the positive electrode active material provided in the present application is a polycrystalline material, which is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected by grain boundaries. The positive electrode active material includes secondary particles, and the secondary particles include a first secondary particle, a second secondary particle, and a third secondary particle, which is prepared once. The lithium-ion secondary battery prepared by the above method has a high compaction density of the positive electrode sheet, and the secondary particles in the positive electrode sheet are not easy to break as the compaction density of the positive electrode sheet increases, so that the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0100] In one embodiment, reference Figure 3 , the preparation method of the positive electrode active material comprises:

[0101] S310: providing a solution containing a nickel source, a cobalt source and a manganese source, wherein the molar ratio of the nickel source, the cobalt source and the manganese source is x:y:(1-xy), and x≥0.85.

[0102] In the embodiment of the present application, the nickel source includes but is not limited to nickel carbonate, nickel hydroxide, nickel acetate, nickel sulfate, nickel chloride, nickel nitrate and nickel oxalate, etc. The cobalt source includes but is not limited to cobalt carbonate, cobalt hydroxide, cobalt acetate, cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt oxalate, etc. The manganese source includes but is not limited to manganese dioxide, electrolytic manganese dioxide, manganese tetraoxide, etc.

[0103] In the embodiments of the present application, x may be 0.85, 0.88, 0.90, 0.92, 0.95, 0.96, 0.98, 0.99, 1, etc., or a range consisting of any two of the above values, such as 0.85-0.92, 0.92-0.96, 0.96-1, etc.

[0104] S320: Add a complexing agent with a concentration of 0.2mol / L to 3.5mol / L and a precipitating agent with a concentration of 0.3mol / L to 0.5mol / L to a solution containing a nickel source, a cobalt source and a manganese source. Under an inert atmosphere, control the pH range to be 12.1 to 13, react at 50°C to 70°C for 4h to 7h to form a first intermediate product.

[0105] In the embodiment of the present application, the precipitant reacts with the nickel source, the cobalt source and the manganese source to generate a precipitate, and the complexing agent can effectively complex the metal ions such as Ni, Co, and Mn in the liquid, which helps to control the composition of the positive electrode active material precursor. The pH range is controlled to be 12.1 to 13. Maintaining a higher pH can inhibit the seed growth of the overall particles and maintain the uniform particle size of the secondary particles. The number of seeds is adjusted by controlling the nucleation time to 4h to 7h; by controlling the concentration of the precipitant and the complexing agent, as well as controlling the pH range, reaction temperature and reaction time, it is beneficial to control the reaction of the nickel source, the cobalt source and the manganese source to generate nickel cobalt manganese hydroxide crystal nuclei. Wherein, the concentration of the complexing agent can be 0.2mol / L, 0.3mol / L, 0.5mol / L, 0.8mol / L, 1mol / L, 1.5mol / L, 1.8mol / L, 2.1mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, etc., or a range consisting of any two of the above values, for example, 0.2mol / L to 1mol / L, 1mol / L to 2.1mol / L, 2.1mol / L to 3.5mol / L, 0.8mol / L to 2.5mol / L, 0.3mol / L to 3mol / L, etc. The concentration of the precipitant can be 0.3 mol / L, 0.32 mol / L, 0.35 mol / L, 0.38 mol / L, 0.40 mol / L, 0.45 mol / L, 0.48 mol / L, 0.5 mol / L, etc., or a range consisting of any two of the above values, such as 0.3 mol / L to 0.38 mol / L, 0.38 mol / L to 0.45 mol / L, 0.45 mol / L to 0.5 mol / L, etc. The pH can be 12.1, 12.2, 12.3, 12.5, 12.6, 12.7, 12.8, 12.9, 13.0, etc., or a range consisting of any two of the above values, such as 12.1 to 12.5, 12.5 to 12.8, 12.8 to 13.0, etc. The reaction temperature can be 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, etc., or a range consisting of any two of the above values, such as 50°C to 58°C, 58°C to 65°C, 65°C to 70°C, etc. The reaction time can be 4h, 4.5h, 4.8h, 5h, 5.2h, 5.5h, 5.7h, 6.0h, 6.3h, 6.5h, 6.6h, 6.8h, 7h, etc., or a range consisting of any two of the above values, such as 4h to 5.2h, 5.2h to 6.3h, 6.3h to 7h, etc. In the embodiment of the present application, the inert atmosphere is nitrogen, and in other embodiments, the inert atmosphere can also be argon, etc.

[0106] S330: The pH of the first intermediate product is adjusted to 10.5-11, and the reaction is carried out for 13h-17h to obtain a second intermediate product.

[0107] In the embodiment of the present application, the pH of the reaction is lowered and adjusted to 10.5-11, so that the reaction transitions from nucleation to growth. Lowering the pH for a short time can reduce the generation of new crystal nuclei and improve the particle size consistency of the secondary particles of nickel cobalt manganese hydroxide. The pH can be 10.5, 10.6, 10.7, 10.8, 10.85, 10.9, 11.0, etc., or a range consisting of any two of the above values, such as 10.5-10.7, 10.7-10.85, 10.85-11.0, etc. The reaction time can be 13 h, 13.5 h, 13.8 h, 14 h, 14.5 h, 15.0 h, 15.6 h, 16.2 h, 16.5 h, 16.8 h, 17 h, etc., or a range consisting of any two of the above values, for example, 13 h to 14.5 h, 14.5 h to 16.2 h, 16.2 h to 17 h, etc.

[0108] S340: adjusting the pH of the second intermediate product to 10-10.4, reacting for 55-80 hours, and obtaining nickel-cobalt-manganese hydroxide, wherein the volume average particle size DV50 of the nickel-cobalt-manganese hydroxide is 8.5 μm-12 μm.

[0109] In the embodiment of the present application, the step of forming nickel-cobalt-manganese hydroxide is the growth period, and maintaining a low pH in the range of 10 to 10.4 can inhibit nucleation and avoid the appearance of small particles. Stable reaction conditions can improve the crystallinity of the overall secondary particles. Among them, the pH can be 10, 10.1, 10.2, 10.3, 10.4, etc., or a range consisting of any two of the above values, such as 10 to 10.2, 10.2 to 10.4, etc. The reaction time can be 55h, 58h, 60h, 65h, 70h, 73h, 75h, 76h, 78h, 80h, etc., or a range consisting of any two of the above values, for example, 55h to 65h, 65h to 76h, 76h to 80h, etc. The volume average particle size DV50 of nickel cobalt manganese hydroxide can be 8.5μm, 8.8μm, 9.0μm, 9.2μm, 9.5μm, 10μm, 11μm, 11.5μm, 12μm, etc., or a range consisting of any two of the above values, for example, 8.5μm~9.5μm, 9.5μm~11μm, 11μm~12μm, etc.

[0110] S350: Mix nickel cobalt manganese hydroxide and lithium salt, and sinter them to obtain lithium nickel cobalt manganese oxide positive electrode material.

[0111] In the embodiment of the present application, nickel cobalt manganese hydroxide and lithium salt are sintered to cause a solid phase reaction to generate a lithium nickel cobalt manganese oxide positive electrode material. The lithium salt is one or a mixture of two or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi. In the embodiment of the present application, the metal molar ratio Li / Me of the lithium salt and the ternary nickel cobalt manganese hydroxide precursor is 1.0 to 1.2, and Me is the total mole of Ni, Co, and Mn elements.

[0112] In this embodiment, the proportion of nickel in the nickel cobalt manganese hydroxide precursor in all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium nickel cobalt manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium ion secondary battery better. By controlling the concentration of the precipitant, the concentration of the complexing agent, the pH, the temperature and the time, the nickel cobalt manganese hydroxide precursor also has the particle size distribution of the secondary particles provided in the first aspect of the present application, and the volume average particle size DV50 of the nickel cobalt manganese hydroxide precursor is controlled to be within the range of 8.5 μm to 12 μm, which helps to further control the volume average particle size DV50 of the lithium nickel cobalt manganese oxide positive electrode material. The lithium nickel cobalt manganese oxide positive electrode material is obtained by sintering nickel cobalt manganese hydroxide with lithium salt.

[0113] In another embodiment, reference Figure 4 , the preparation method of the positive electrode active material comprises:

[0114] S410: providing a solution containing a nickel source, a cobalt source and a manganese source, wherein the molar ratio of the nickel source, the cobalt source and the manganese source is x:y:(1-xy), and x≥0.85.

[0115] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0116] S420: Add a complexing agent with a concentration of 0.2mol / L to 3.5mol / L and a precipitating agent with a concentration of 0.3mol / L to 0.5mol / L to a solution containing a nickel source, a cobalt source and a manganese source, and under an inert atmosphere, control the pH range to be 12.1 to 13, and react at 50°C to 70°C for 4h to 7h to form a first intermediate product.

[0117] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0118] S430: The pH of the first intermediate product is adjusted to 10.5-11, and the reaction is carried out for 13-17 hours to obtain a second intermediate product.

[0119] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0120] S440: adjusting the pH of the second intermediate product to 10-10.4, reacting for 55-80 hours, and obtaining nickel-cobalt-manganese hydroxide, wherein the volume average particle size DV50 of the nickel-cobalt-manganese hydroxide is 8.5 μm-12 μm.

[0121] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0122] S450: Mix nickel-cobalt-manganese hydroxide and lithium salt, and perform the first sintering to obtain the first product.

[0123] In an embodiment of the present application, nickel cobalt manganese hydroxide is mixed with a lithium salt and subjected to a first high-temperature sintering to obtain a first product; the first product is mixed with a first coating source and subjected to a second sintering to obtain a second product, and the second product is a lithium nickel cobalt manganese oxide positive electrode material whose surface is coated with the first coating source.

[0124] In one embodiment of the present application, the temperature of the first sintering is 725°C to 780°C, and the time of the first sintering is 7h to 14h. In this embodiment, the first sintering temperature and time, the second sintering temperature and time are controlled within the above ranges, respectively, so that the material has a better crystallization state, thereby improving the electrochemical properties of the lithium nickel cobalt manganese oxide positive electrode material. The temperature of the first sintering can be 725°C, 735°C, 746°C, 755°C, 770°C, 775°C, 780°C, etc., or a range value composed of any two of the above values, for example, 720°C to 735°C, 735°C to 755°C, 755°C to 780°C, 710°C to 746°C, 720°C to 770°C, 746°C to 780°C, etc. The time of the first sintering can be 7h, 7.5h, 8.2h, 8.8h, 9.2h, 10h, 12h, 14h, etc., or a range value formed by any two of the above values, for example, 7h~9.2h, 9.2h~14h, 8.2h~12h, etc.

[0125] In another embodiment of the present application, nickel cobalt manganese hydroxide, lithium salt and doping source are mixed and sintered for the first time to obtain a first product, wherein the doping source includes one or more of Mg source, Na source, Zr source, Y source, Al source, Ca source, W source, Nb source, Ta source, Sr source or Ti source. In this embodiment, one or more of Mg source, Na source, Zr source, Y source, Al source, Ca source, W source, Nb source, Ta source, Sr source or Ti source are added to the positive electrode active material to improve the crystal structure of the material and reduce the distortion of the layered structure, thereby improving the structural stability and cycle life of the lithium nickel cobalt manganese oxide positive electrode material.

[0126] S460: Mix the first product with the first coating source, and perform a second sintering to obtain a second product, wherein the temperature of the second sintering is lower than the temperature of the first sintering.

[0127] In the embodiment of the present application, after secondary sintering, the material has a better crystal state, thereby improving the electrochemical performance of the lithium nickel cobalt manganese oxide positive electrode material. The coating layer formed by the first coating source can also reduce the possibility of side reactions between the lithium nickel cobalt manganese oxide positive electrode material and the electrolyte, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0128] In the embodiment of the present application, the temperature of the second sintering is 400°C to 615°C, and the time of the second sintering is 5h to 11h. The temperature of the second sintering can be 400°C, 420°C, 480°C, 540°C, 580°C, 615°C, etc., or a range value composed of any two of the above values, for example, 400°C to 540°C, 540°C to 650°C, 480°C to 580°C, 420°C to 615°C, etc. The time of the second sintering can be 5h, 6.5h, 8.2h, 8.7h, 9.2h, 11h, etc., or a range value composed of any two of the above values, for example, 5h to 8.7h, 8.7h to 11h, 6.5h to 9.2h, etc.

[0129] In the embodiment of the present application, a coating layer can be formed on the surface of the lithium nickel cobalt manganese oxide by sintering twice, which can improve the electrochemical performance of the lithium ion secondary battery.

[0130] In yet another embodiment of the present application, refer to Figure 5 , the preparation method of the positive electrode active material comprises:

[0131] S510: providing a solution containing a nickel source, a cobalt source and a manganese source, wherein the molar ratio of the nickel source, the cobalt source and the manganese source is x:y:(1-xy), and x≥0.85.

[0132] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0133] S520: Add a complexing agent with a concentration of 0.2mol / L to 3.5mol / L and a precipitating agent with a concentration of 0.3mol / L to 0.5mol / L to a solution containing a nickel source, a cobalt source and a manganese source, and under an inert atmosphere, control the pH range to be 12.1 to 13, and react at 50°C to 70°C for 4h to 7h to form a first intermediate product.

[0134] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0135] S530: The pH of the first intermediate product is adjusted to 10.5-11, and the reaction is carried out for 13h-17h to obtain a second intermediate product.

[0136] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0137] S540: adjusting the pH of the second intermediate product to 10-10.4, reacting for 55-80 hours, and obtaining nickel-cobalt-manganese hydroxide, wherein the volume average particle size DV50 of the nickel-cobalt-manganese hydroxide is 8.5 μm-12 μm.

[0138] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0139] S550: Mix nickel-cobalt-manganese hydroxide and lithium salt, and obtain the first product after the first sintering.

[0140] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0141] S560: Mix the first product with the first coating source, and perform a second sintering to obtain a second product. The temperature of the second sintering is lower than the temperature of the first sintering.

[0142] The steps are the same as those in the above embodiment and will not be explained in detail here.

[0143] S570: Mix the second product with the second coating source, and sinter for a third time to obtain a third product, which is a lithium nickel cobalt manganese oxide positive electrode material.

[0144] In the embodiment of the present application, a coating can be further formed on the surface of the lithium nickel cobalt manganese oxide by the third sintering. In the embodiment of the present application, the second coating source includes the first one or more of the B source, Al source, and Y source, which is beneficial to improving the interface stability of the positive electrode active material and improving the deintercalation ability of lithium ions. Among them, the B source can refine the primary grains and improve the deintercalation ability of lithium ions on the surface. The coating formed by the Y source is easy to form a protective layer on the surface, reduce the surface activity, and improve the interface stability.

[0145] In one embodiment, the temperature of the third sintering is 250°C to 348°C, and the time of the third sintering is 5h to 12h; the second coating source includes the first one or more of the B source, the Al source, and the Y source. Among them, the temperature of the third sintering can be 250°C, 268°C, 275°C, 280°C, 300°C, 320°C, 335°C, 348°C, etc., or a range value composed of any two of the above values, for example, 250°C to 280°C, 280°C to 320°C, 320°C to 348°C, etc. The time of the third sintering can be 5h, 5.5h, 6.8h, 8.8h, 9.2h, 10h, 12h, etc., or a range value composed of any two of the above values, for example, 5h to 8.8h, 8.8h to 12h, 6.8h to 10h, etc.

[0146] In the embodiments of the present application, by performing three sinterings and controlling the sintering temperature within the above range, a coating material formed by coating the lithium nickel cobalt manganese oxide with two coating sources can be obtained, which can improve the electrochemical performance of the lithium ion secondary battery.

[0147] The third aspect of the present application further provides a positive electrode active material, including lithium nickel cobalt manganese oxide, wherein the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include: the first type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N1, 2% ≤ N1 < 10%; the second type of secondary particles, the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N2, 70% ≤ N2 < 85%; the third type of secondary particles, the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the proportion of the number of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

[0148] In this embodiment, the proportion of nickel element in the nickel cobalt manganese hydroxide precursor in all transition metal elements is controlled within the range of greater than or equal to 0.85, so that the nickel element in the lithium nickel cobalt manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium ion secondary battery better. The secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm. The positive electrode active material provided by the present application is a polycrystalline material, and the polycrystalline material is composed of many grains with different orientations, that is, primary particles, and the grains are interconnected through grain boundaries. The positive electrode active material includes secondary particles, and the secondary particles include the first type of secondary particles, the second type of secondary particles, and the third type of secondary particles, and these secondary particles are prepared at one time. The lithium ion secondary battery prepared by using the above method has a higher tap density of the positive electrode sheet, and the secondary particles in the positive electrode sheet are not easily broken as the tap density of the positive electrode sheet increases, so that the lithium ion secondary battery has a high volumetric energy density, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0149] In one embodiment, one or two or three of the first type of secondary particles, the second type of secondary particles, and the third type of secondary particles are circular secondary particles, and for the circular secondary particles, in the scanning electron microscope image, the ratio of the volume particle size distribution of the secondary particles to the shortest diameter is d1 / d2, 1 ≤ d1 / d2 ≤ 1.2.

[0150] In the present embodiment, one, two or three of the first secondary particles, the second secondary particles, and the third secondary particles are round secondary particles, and the ratio of their longest diameter to their shortest diameter is within the above range, so that the internal arrangement of the secondary particles is more ordered, the friction between the secondary particles is reduced, and the compaction density is greater under the same pressure; during the cyclic charge and discharge process, the degree of stress accumulation inside the round secondary particles is lower, and the generated stress is easier to release, reducing the probability of secondary particle breakage, so that the lithium-ion secondary battery has a high volume energy density, thereby improving the electrochemical performance of the lithium-ion secondary battery.

[0151] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O n material; 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤n≤2.2, M1 includes a combination of one or more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, and Ti.

[0152] In this embodiment, the positive electrode active material combines the advantages of the three elements of nickel, cobalt and manganese. At the same time, the doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and promote the growth of radial primary particles, thereby improving the electrochemical properties of the positive electrode active material.

[0153] The fourth aspect of the present application further provides a method for preparing a positive electrode active material, including: providing a solution containing a nickel source, a cobalt source, and a manganese source, wherein the molar ratio of the nickel source, the cobalt source, and the manganese source is x:y:(1-x-y), and x≥0.85; adding a complexing agent with a concentration of 0.2 mol / L to 3.5 mol / L and a precipitating agent with a concentration of 0.3 mol / L to 0.5 mol / L into the solution containing the nickel source, the cobalt source, and the manganese source, controlling the pH range to be 12.1 to 13 under an inert atmosphere, reacting at 50 to 70 °C for 4 h to 7 h to form a first intermediate product; adjusting the pH of the first intermediate product to 10.5 to 11 and reacting for 13 h to 17 h to obtain a second intermediate product; adjusting the pH of the second intermediate product to 10 to 10.4 and reacting for 55 h to 80 h to obtain nickel cobalt manganese hydroxide, and the volume average particle size DV50 of the nickel cobalt manganese hydroxide is 8.5 μm to 12 μm; mixing the nickel cobalt manganese hydroxide with a lithium salt and sintering to obtain a lithium nickel cobalt manganese oxide positive electrode material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; the secondary particles include a first type of secondary particles, a second type of secondary particles, and a third type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the number proportion of the first type of secondary particles is N1, 2% ≤ N1 < 10%; the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the number proportion of the second type of secondary particles is N2, 70% ≤ N2 < 85%; the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the number proportion of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

[0154] In this embodiment, the proportion of nickel in the nickel-cobalt-manganese hydroxide precursor to all transition metal elements is controlled to be greater than or equal to 0.85, so that the nickel in the subsequently prepared lithium-nickel-cobalt-manganese positive electrode active material accounts for at least 0.85 of all transition metal elements, thereby making the electrochemical performance of the lithium-ion secondary battery better. In the preparation process of the nickel-cobalt-manganese hydroxide precursor, the precipitant reacts with the nickel source, the cobalt source and the manganese source to generate a precipitate, and the complexing agent can effectively complex metal ions such as Ni, Co, and Mn in the liquid, which helps to control the composition of the positive active material precursor. The concentration of the mixed salt solution, the concentration of the precipitant, the concentration of the complexing agent, the pH, the temperature and the time are controlled within the above range, so that the nickel-cobalt-manganese hydroxide precursor has the particle size distribution of the secondary particles provided in the first aspect of the present application. Specifically, in the first intermediate product stage, the pH is controlled in the range of 12.1 to 13. Maintaining a higher pH can inhibit the seed growth of the overall particles and maintain the uniform particle size of the secondary particles. The number of seeds is adjusted by controlling the nucleation time to 4h to 7h; in the second intermediate product stage, the pH of the reaction is reduced and the pH is adjusted to 10.5 to 11, so that the reaction transitions from nucleation to growth. Reducing the pH in a short time can reduce the generation of new nuclei and improve the consistency of the particle size of the secondary particles; the nickel cobalt manganese hydroxide stage is the growth period, and maintaining a low pH in the range of 10 to 10.4 can inhibit nucleation and avoid the appearance of small particles. Stable reaction conditions can improve the crystallinity of the overall secondary particles. The preparation method of the positive electrode active material provided in the fourth aspect of the present application is the same as the preparation method of the positive electrode active material in the lithium ion secondary battery in the third aspect.

[0155] The fifth aspect of the present application provides an electrical device, including any of the above lithium-ion secondary batteries, or / and, a lithium-ion secondary battery prepared by any of the above preparation methods, or / and any of the above positive electrode active materials, or / and, a positive electrode active material prepared by any of the above methods for preparing positive electrode active materials. The electrical device of the embodiment of the present application has at least the same advantages as the lithium-ion secondary battery of the first aspect, or / and at least the same advantages as the lithium-ion secondary battery prepared by the method for preparing the lithium-ion secondary battery of the second aspect, or / and at least the same advantages as the positive electrode active material of the third aspect, or / and at least the same advantages as the positive electrode active material prepared by the method for preparing the positive electrode active material of the fourth aspect.

[0156] Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0157] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material composition of the above embodiment of the present application.

[0158] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0159] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0160] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0161] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0162] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0163] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the negative electrode active material of the above embodiment.

[0164] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0165] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0166] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0167] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0168] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0169] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0170] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0171] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.

[0172] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0173] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0174] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0175] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0176] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0177] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.

[0178] In some embodiments, Figure 6 As shown, the battery cell 10 may include an outer package. The outer package may be used to encapsulate the battery cell assembly 11 and the electrolyte. The outer package includes an end cap 12, a housing 13 and other functional components.

[0179] The end cap 12 refers to a component that covers the opening of the shell 13 to isolate the internal environment of the battery cell 10 from the external environment. Without limitation, the shape of the end cap 12 can be adapted to the shape of the shell 13 to match the shell 13. Optionally, the end cap 12 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 12 is not easily deformed when squeezed and collided, so that the battery cell 10 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 12a can be provided on the end cap 12. The electrode terminal 12a can be used to electrically connect to the battery cell assembly 11 for outputting or inputting electrical energy of the battery cell 10. In some embodiments, the end cap 12 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 10 reaches a threshold. The material of the end cap 12 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member (not shown) may be provided inside the end cap 12 to isolate the electrical connection components in the housing 13 from the end cap 12 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0180] The shell 13 is a component used to cooperate with the end cap 12 to form the internal environment of the battery cell 10, wherein the formed internal environment can be used to accommodate the battery cell assembly 11, electrolyte and other components. The shell 13 and the end cap 12 can be independent components, and an opening can be set on the shell 13, and the internal environment of the battery cell 10 is formed by covering the opening with the end cap 12 at the opening. Without limitation, the end cap 12 and the shell 13 can also be integrated. Specifically, the end cap 12 and the shell 13 can form a common connection surface before other components are put into the shell, and when the interior of the shell 13 needs to be encapsulated, the end cap 12 covers the shell 13. The shell 13 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 13 can be determined according to the specific shape and size of the battery cell assembly 11. The material of the shell 13 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0181] The housing 13 may contain one or more battery cell assemblies 11. The portions of the positive electrode sheet and the negative electrode sheet that do not have active materials each constitute a tab 11a. The positive tab and the negative tab may be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 11a connects the electrode terminal to form a current loop.

[0182] Please refer to Figure 7The battery 100 includes a box body 20 and a battery cell 10, and the battery cell 10 is contained in the box body 20. The box body 20 is used to provide a storage space for the battery cell 10, and the box body 20 can adopt a variety of structures. In some embodiments, the box body 20 may include a first part 21 and a second part 22, and the first part 21 and the second part 22 cover each other, and the first part 21 and the second part 22 jointly define a storage space for accommodating the battery cell 10. The second part 22 may be a hollow structure with one end open, and the first part 21 may be a plate-like structure, and the first part 21 covers the open side of the second part 22, so that the first part 21 and the second part 22 jointly define a storage space; the first part 21 and the second part 22 may also be hollow structures with one side open, and the open side of the first part 21 covers the open side of the second part 22. Of course, the box body 20 formed by the first part 21 and the second part 22 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0183] In the battery 100, there may be multiple battery cells 10, and the multiple battery cells 10 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 10 are both connected in series and in parallel. The multiple battery cells 10 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 10 is accommodated in the box 20; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 10 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 20. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 10.

[0184] The battery 100 in the embodiment of the present application includes a lithium-ion battery as a battery cell 10. In other embodiments, the battery 100 may further include any one or more of a lithium-sulfur battery, a sodium-ion battery, and a magnesium-ion battery, but is not limited thereto. The battery cell 10 may be cylindrical, flat, rectangular, or in other shapes.

[0185] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0186] The electrical equipment includes at least one of the battery cells and / or batteries provided in the present application. The battery cells or battery packs can be used as power sources for electrical equipment, or as energy storage units for electrical equipment. Electrical equipment can include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0187] As an electrical device, a battery cell and / or a battery can be selected according to its usage requirements.

[0188] Figure 8a and Figure 8b As shown, the electrical equipment is a vehicle such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. A schematic diagram of the structure of a vehicle 1000 is specifically provided. A battery 100 is arranged inside the vehicle 1000, and the battery 100 can be arranged at the bottom, head or tail of the vehicle 1000. The battery 100 can be used to power the vehicle 1000. For example, the battery 100 can be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to power the motor 300, for example, for the starting, navigation and driving power requirements of the vehicle 1000.

[0189] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0190] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0191] Example 1

[0192] 1) Preparation of positive electrode active materials:

[0193] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0194] Before the reaction begins, add clean water to the reactor, heat it to 60°C, and add a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.93:0.06:0.01 among Ni, Co, and Mn. Then add 0.4 mol / L of sodium carbonate (complexing agent) and 0.4 mol / L of ammonia water (precipitant), and in a nitrogen atmosphere, control the pH in the reactor at 13 and the temperature at 55°C to perform a coprecipitation reaction. After 5 hours of reaction, a first intermediate product is formed;

[0195] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 10.8, react for 16 hours, and obtain the second intermediate product;

[0196] Then, the complexing agent and ammonia water were added to obtain a pH of 10.2 in the reactor, and the reaction was continued for 60 hours to obtain nickel-cobalt-manganese hydroxide. The particles of nickel-cobalt-manganese hydroxide grew to a target Dv50 of about 10 μm. After the reaction was completed, the nickel-cobalt-manganese strong oxide precursor (Ni 0.93 Co 0.06 Mn 0.01 (OH)2).

[0197] 1.2) First sintering:

[0198] The nickel-cobalt-manganese strong oxide precursor was mixed with LiOH in a molar ratio of 1:1.05, and then SrO and ZrO2 were added to make the molar ratio of Li, Sr, and Zr be 1:0.0004:0.0006. The mixed powder was then added to a sintering furnace for the first sintering, kept at 725°C for 13h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a lithium transition metal oxide (Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2).

[0199] 1.3) Second sintering:

[0200] The lithium transition metal oxide obtained in step 1.2) was crushed and mixed with CoOOH and Al2O3 so that the molar ratio of Li, Co and Al was 1:0.011:0.005, and the mixed powder was added into a sintering furnace for a second sintering at a temperature of 615°C for 7.5h, and then cooled to room temperature at a rate of 5°C / min.

[0201] 1.4) 300 g of the powder obtained in step 1.3) was added to 300 mL of deionized water and stirred for 5 min, then filtered to obtain a solid powder, which was then dried at 60° C. under forced air.

[0202] 1.5) The third sintering:

[0203] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with Y2O3 and H2BO3 to make the molar ratio of lithium element, yttrium element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 348°C for 6h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2.

[0204] 2) Preparation of positive electrode.

[0205] The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) prepared above are dissolved in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 98:0.5:1.5, and are fully stirred and mixed to obtain a positive electrode slurry; then the positive electrode slurry is evenly coated on an aluminum foil, dried and cold pressed to obtain a positive electrode sheet.

[0206] 3) Preparation of negative electrode materials.

[0207] Artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) are added to deionized water solvent in a mass ratio of 90:5:2:2:1, stirred and mixed thoroughly, and then coated on both sides of copper foil, dried, cold pressed and other processes to obtain a negative electrode sheet.

[0208] 4) Preparation of electrolyte.

[0209] The electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC), wherein the volume ratio of EC, DEC and DMC is 1:1:1. Then LiPF6 is dissolved in the above organic solvent, wherein the concentration of LiPF6 is 1 mol / L.

[0210] 5) Isolation film.

[0211] A 13μm thick polyethylene isolation film was selected.

[0212] 6) Preparation of lithium-ion batteries.

[0213] The separator, negative electrode sheet and positive electrode sheet are stacked in the order of "separator-negative electrode sheet-separator-positive electrode sheet", processed into shape, packaged in aluminum-plastic bags, injected with electrolyte, and formed after packaging to obtain a soft-pack battery.

[0214] Example 2

[0215] Similar to Example 1, except that:

[0216] 1) Preparation of positive electrode active materials:

[0217] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0218] Before the reaction begins, add clean water to the reactor, heat it to 60°C, and add a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.85:0.14:0.01 among Ni, Co, and Mn. Then add 0.4 mol / L of sodium carbonate (complexing agent) and ammonia water (0.5 mol / L) (ammonia water is a precipitant), and in a nitrogen atmosphere, control the pH in the reactor at 12.1 and the temperature at 70°C to carry out a coprecipitation reaction. After 4 hours of reaction, a first intermediate product is formed;

[0219] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 10.8, react for 13 hours, and obtain the second intermediate product;

[0220] Then, the complexing agent and ammonia water were added to make the pH in the reactor equal to 10.2, and the reaction was continued for 55 hours to obtain nickel-cobalt-manganese hydroxide. The particles of nickel-cobalt-manganese hydroxide grew to the target Dv50 of about 8.5 μm. After the reaction was completed, the nickel-cobalt-manganese strong oxide precursor (Ni 0.85 Co 0.14 Mn 0.01 (OH)2).

[0221] 1.2) First sintering:

[0222] The nickel-cobalt-manganese strong oxide precursor was mixed with LiOH in a molar ratio of 1:1.05, and then SrO and ZrO2 were added to make the molar ratio of Li, Sr, and Zr be 1:0.0004:0.0006. The mixed powder was then added to a sintering furnace for the first sintering, kept at 725°C for 7h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a lithium transition metal oxide (Li(Ni 0.85 Co 0.14 Mn 0.01 ) 0.999 Sr 0.00004 Zr 0.0006 O2).

[0223] 1.3) Second sintering:

[0224] The lithium transition metal oxide obtained in step 1.12) was crushed and mixed with CoOOH and Al2O3 to make the molar ratio of Li, Co and Al be 1:0.011:0.005, and the mixed powder was added into a sintering furnace for a second sintering at a temperature of 615°C for 5h, and then cooled to room temperature at a rate of 5°C / min.

[0225] 1.4) 300 g of the powder obtained in step 1.13) was added to 300 mL of deionized water and stirred for 5 min, then filtered to obtain a solid powder, which was then dried at 60° C. under forced air.

[0226] 1.5) The third sintering:

[0227] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with Y2O3 and H2BO3 to make the molar ratio of lithium element, yttrium element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 250°C for 5h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.85 Co 0.14 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2.

[0228] Example 3

[0229] Similar to Example 1, except that:

[0230] 1) Preparation of positive electrode active materials:

[0231] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0232] Before the reaction begins, add clean water to the reactor, heat it to 60°C, and add a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.9:0.09:0.01 among Ni, Co, and Mn. Then add 0.2 mol / L of sodium carbonate and ammonia water (0.4 mol / L), and in a nitrogen atmosphere, control the pH in the reactor at 12.5 and the temperature at 58°C to perform a coprecipitation reaction. After 7 hours of reaction, a first intermediate product is formed;

[0233] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 11, react for 17 hours, and obtain the second intermediate product;

[0234] Then, the complexing agent and ammonia water were added to make the pH in the reactor equal to 10.4, and the reaction was continued for 80 hours to obtain nickel-cobalt-manganese hydroxide. The particles of nickel-cobalt-manganese hydroxide grew to the target Dv50 of about 12 μm. After the reaction was completed, the nickel-cobalt-manganese strong oxide precursor (Ni 0.9 Co 0.09 Mn 0.01 (OH)2).

[0235] 1.2) First sintering:

[0236] The nickel-cobalt-manganese strong oxide precursor was mixed with LiOH in a molar ratio of 1:1.05, and then SrO and ZrO2 were added to make the molar ratio of Li, Sr, and Zr be 1:0.0004:0.0006. The mixed powder was then added to a sintering furnace for the first sintering, kept at 780°C for 14h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a lithium transition metal oxide (Li(Ni 0.9 Co 0.09 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2).

[0237] 1.3) Second sintering:

[0238] The lithium transition metal oxide obtained in step 1.2) was crushed and mixed with CoOOH and Al2O3 so that the molar ratio of Li, Co and Al was 1:0.011:0.005. The mixed powder was added into a sintering furnace for a second sintering. The sintering temperature was kept at 400°C for 11 hours, and then cooled to room temperature at a rate of 5°C / min.

[0239] 1.4) 300 g of the powder obtained in step 1.3) was added to 300 mL of deionized water and stirred for 5 min, then filtered to obtain a solid powder, which was then dried at 60° C. under forced air.

[0240] 1.5) The third sintering:

[0241] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with Y2O3 and H2BO3 to make the molar ratio of lithium element, yttrium element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 348°C for 12h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.9 Co 0.09 Mn 0.01 ) 0.999 Sr 0.0004Zr 0.0006 O2.

[0242] Example 4

[0243] Same as Example 1, except that:

[0244] 1) Preparation of positive electrode active materials:

[0245] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0246] Before the reaction begins, add clean water to the reactor, heat it to 60°C, and add a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 0.95:0.04:0.01 among Ni, Co, and Mn. Then add 3.5 mol / L of sodium carbonate and ammonia water (0.35 mol / L), and in a nitrogen atmosphere, control the pH in the reactor at 13 and the temperature at 50°C to perform a coprecipitation reaction. After 5 hours of reaction, a first intermediate product is formed;

[0247] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 10.6, react for 15.5 hours, and obtain the second intermediate product;

[0248] Then, the complexing agent and ammonia water were added to make the pH in the reactor equal to 10, and the reaction was continued for 60 hours to obtain nickel-cobalt-manganese hydroxide. The particles of nickel-cobalt-manganese hydroxide grew to the target Dv50 of about 10 μm. After the reaction was completed, the nickel-cobalt-manganese strong oxide precursor (Ni 0.95 Co 0.04 Mn 0.01 (OH)2).

[0249] Example 5

[0250] Same as Example 1, except that:

[0251] 1) Preparation of positive electrode active materials:

[0252] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0253] Before the reaction begins, clean water is added to the reactor, the temperature is raised to 60°C, and a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate is added in a molar ratio of 0.93:0.06:0.01 among Ni, Co, and Mn. Then, 2.1 mol / L of sodium carbonate and ammonia water (0.4 mol / L) are added, and the pH in the reactor is controlled at 13 and the temperature at 55°C under a nitrogen atmosphere to perform a coprecipitation reaction. After 5 hours of reaction, a first intermediate product is formed;

[0254] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 10.8, react for 16 hours, and obtain the second intermediate product;

[0255] Then, the complexing agent and ammonia water were added to make the pH in the reactor 10.3, and the reaction was continued for 65 hours to obtain nickel cobalt manganese hydroxide. The particles of nickel cobalt manganese hydroxide grew to the target Dv50 of about 9.5 μm. After the reaction was completed, the nickel cobalt manganese strong oxide precursor (Ni 0.93 Co 0.06 Mn 0.01 (OH)2).

[0256] Example 6

[0257] Same as Example 1, except that:

[0258] 1) Preparation of positive electrode active materials:

[0259] 1.2) First sintering:

[0260] The nickel-cobalt-manganese strong oxide precursor was mixed with Li2OH3 at a molar ratio of 1:1.05, and then Sb2O3 and ZrO2 were added to make the molar ratio of Li, Sb, and Zr be 1:0.0008:0.0006. The mixed powder was then added to a sintering furnace for the first sintering, kept at 735°C for 12h, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a lithium transition metal oxide (Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.9986 Sb 0.0008 Zr 0.0006 O2).

[0261] Example 7

[0262] Same as Example 1, except that:

[0263] 1) Preparation of positive electrode active materials:

[0264] 1.3) Second sintering:

[0265] The lithium transition metal oxide obtained in step 1.2) is crushed and mixed with CoOOH and Ti2O3 so that the molar ratio of Li, Co and Ti is 1:0.011:0.005. The mixed powder is added into a sintering furnace for a second sintering. The sintering temperature is 500°C for 10 hours, and then cooled to room temperature at a rate of 5°C / min.

[0266] Example 8

[0267] Same as Example 1, except that:

[0268] 1) Preparation of positive electrode active materials:

[0269] 1.5) The third sintering:

[0270] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with H2BO3 and Al2O3 to make the molar ratio of lithium element, aluminum element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 300°C for 7h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2.

[0271] Comparative Example 1

[0272] Same as Example 1, except that:

[0273] 1) Preparation of positive electrode active materials:

[0274] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0275] Before the reaction begins, clean water is added to the reactor, the temperature is raised to 60°C, and a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate is added in a molar ratio of 0.93:0.06:0.01 among Ni, Co, and Mn. Then, 0.8 mol / L of sodium carbonate and ammonia water (0.25 mol / L) are added, and the pH in the reactor is controlled at 11.5 and the temperature is controlled at 64°C under a nitrogen atmosphere to perform a coprecipitation reaction. After 6 hours of reaction, the first intermediate product is formed;

[0276] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 10.2, react for 17 hours, and obtain the second intermediate product;

[0277] Then, the complexing agent and ammonia water were added to make the pH in the reactor 9.6, and the reaction was continued for 65 hours to obtain nickel cobalt manganese hydroxide. The particles of nickel cobalt manganese hydroxide grew to the target Dv50 of about 12 μm. After the reaction was completed, the nickel cobalt manganese strong oxide precursor (Ni 0.93 Co 0.06 Mn 0.01 (OH)2).

[0278] 1.5) The third sintering:

[0279] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with Y2O3 and H2BO3 to make the molar ratio of lithium element, yttrium element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 350°C for 6h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2.

[0280] Comparative Example 2

[0281] Same as the embodiment, except that:

[0282] 1) Preparation of positive electrode active materials:

[0283] 1.1) Preparation of nickel-cobalt-manganese hydroxide precursor:

[0284] Before the reaction begins, clean water is added to the reactor, the temperature is raised to 60°C, and a mixed solution of nickel sulfate, cobalt sulfate, and manganese sulfate is added in a molar ratio of 0.93:0.06:0.01 among Ni, Co, and Mn. Then, 0.8 mol / L of sodium carbonate and ammonia water (0.55 mol / L) are added, and the pH in the reactor is controlled at 14 and the temperature at 61°C under a nitrogen atmosphere to perform a coprecipitation reaction. After 4 hours of reaction, the first intermediate product is formed;

[0285] Continue to add the complexing agent and ammonia water, control the pH in the reactor to gradually decrease, so that the pH in the reactor is 11.5, react for 13 hours, and obtain the second intermediate product;

[0286] Then, the complexing agent and ammonia water were added to make the pH in the reactor 10.6, and the reaction was continued for 58 hours to obtain nickel cobalt manganese hydroxide. The particles of nickel cobalt manganese hydroxide grew to the target Dv50 of about 10 μm. After the reaction was completed, the nickel cobalt manganese strong oxide precursor (Ni 0.93 Co 0.06 Mn 0.01 (OH)2).

[0287] 1.5) The third sintering:

[0288] The powder obtained in step 1.4) was added into a sintering furnace and fully mixed with Y2O3 and H2BO3 to make the molar ratio of lithium element, yttrium element and boron element be 1:0.005:0.003. The mixed powder was sintered for the third time at 350°C for 6h and cooled to room temperature at a rate of 1.5°C / min to obtain the positive electrode active material Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.999 Sr 0.0004 Zr 0.0006 O2.

[0289] Furthermore, the number proportion N1 of the first secondary particles in Examples 1 to 8 and Comparative Examples 1 and 2, the number proportion N2 of the second secondary particles, the ratio d1 / d2 of the longest diameter to the shortest diameter of the second secondary particles, the number proportion N3 of the third secondary particles, the ratio d1 / d2 of the longest diameter to the shortest diameter of the third secondary particles, the ratio N2 / N1 of the number of the second secondary particles to the number of the first secondary particles, the average particle size of the primary particles, and the specific surface area of ​​the positive electrode active material are recorded in Table 2.

[0290] The lithium ion secondary batteries obtained in the above Examples 1 to 8 and Comparative Examples 1 and 2 were subjected to battery performance tests. The detailed process and performance parameters are shown in Tables 1 and 2.

[0291] Test method:

[0292] 1. 0.1C specific capacity test

[0293] Under a constant temperature environment of 25°C, charge to 4.25V at 0.1C, then charge at a constant voltage at 4.25V to a current ≤0.05mA, let stand for 5min, and then discharge to 2.8V at 0.1C to obtain a capacity C1. The specific capacity is C1 / m, where m is the mass of the positive electrode active material.

[0294] 2. 25℃ Cyclic Performance Test

[0295] At a constant temperature of 25°C, charge to 4.25V at 0.33C, then charge at a constant voltage at 4.25V to a current ≤0.05mA, let stand for 5 minutes, and then discharge to 2.8V at 0.33C to obtain a capacity of D1. Repeat the previous process, and record the capacity D100 of the soft-pack battery after 100 cycles. The capacity retention rate after 100 cycles = D100 / D1.

[0296] 3. Laser particle size test

[0297] ① Prepare the sample powder, add surfactant and deionized water, and use ultrasound to ensure that the sample is completely dispersed in the dispersant;

[0298] ② Adjust the test instrument and align it with the sample, inject the sample into the laser particle size analyzer test pool, ensure the suspension state is stable, turn on the light source, and the particles are irradiated by the laser beam. By receiving and measuring the energy distribution of the scattered light, the particle size distribution characteristics of the particles can be obtained. Instrument model: Master Size 3000Hydro EV / Hydro 2000MU.

[0299] 4. Powder compaction density test

[0300] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, set different pressures, and read the thickness of the powder under different pressures (thickness after pressure relief) on the equipment, from which the compaction density can be calculated. Instrument model: CARVER4350.

[0301] 5. Specific surface area test

[0302] The sample to be tested is prepared into a uniform powder or granular form, then placed in a vacuum and set to a specific treatment temperature to remove the gas and moisture adsorbed on the surface. The sample is placed in an adsorption instrument, the liquid nitrogen temperature is set to 77.35K, and the adsorption isotherm is measured by gradually increasing the nitrogen pressure. According to the adsorption isotherm data, the BET equation is used for fitting to obtain the slope and intercept of the adsorption isotherm. According to the parameters in the BET equation, the specific surface area of ​​the sample is calculated.

[0303] 6. Pole compaction density test method

[0304] After the positive electrode active material is prepared into a pole piece, the length L0 is measured, and it is placed on a roller press for rolling under different pressures, and the pole piece length L1, coating material thickness L2, and unit surface area of ​​the pole piece coating material mass M1 are measured after rolling. The compaction P1 under the corresponding pressure is: P1 = M1 / L2, and the elongation Q1 = (L1-L0) / L0. According to the test compaction under different elongations, the pole piece compaction density corresponding to 0.7% elongation can be fitted.

[0305] 7. Average particle size of primary particles

[0306] The positive electrode active material was tested using a ZEISS sigma 300 scanning electron microscope, and then tested according to the standard JY / T010-1996 to observe the sample morphology.

[0307] Software name: LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The scanning electron microscope image of the positive electrode active material is used to automatically identify the single crystal particles by LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The particle outline, particle quantity, number, area, maximum caliper diameter, average number, and manual intervention can be drawn. The average particle size of the primary particle = the sum of all measured particle sizes / the sum of all measured primary particle numbers.

[0308] 8. Volume energy density test

[0309] Using the Blue Electric test system at a constant temperature of 25°C, charge to 4.25V at 0.1C, then charge at 4.25V at a constant voltage until the current is ≤0.05mA, let stand for 5 minutes, and then discharge to 2.8V at 0.1C. The capacity of the cell is C1, and the voltage platform corresponding to the cell is U1. The volume of the cell is measured as V1, and the volume energy density Vd is: Vd = (Cp × U1) / V1.

[0310]

[0311]

[0312] According to the test results in Table 1 and Table 2, the secondary particles in the positive electrode active materials of Examples 1 to 8 include secondary particles of three different particle sizes, and the compaction density of the positive electrode active material, the compaction density of the positive electrode sheet, the specific capacity, the cycle capacity retention rate and the volume energy density are all stronger than those of Comparative Examples 1 and 2. The electrochemical performance of the lithium ion secondary batteries of Examples 1 to 8 is stronger than that of Comparative Examples 1 and 2, indicating that the particle size and number distribution of the secondary particles provided in the embodiments of the present application can improve the compaction density of the positive electrode active material, the compaction density and the energy density of the positive electrode sheet, and the particle size and number distribution of the secondary particles make it difficult for the secondary particles to break as the compaction density of the positive electrode sheet increases, thereby enabling the lithium ion secondary battery to have a higher specific capacity, cycle capacity retention rate and volume energy density, thereby improving the electrochemical performance of the lithium ion secondary battery.

[0313] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: It includes a positive electrode plate, a negative electrode plate and an electrolyte. The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes lithium nickel cobalt manganese oxide. The molar content of nickel element in all transition metal elements is greater than or equal to 0.

85. The positive electrode active material includes secondary particles, and the secondary particles include primary particles. The average particle size of the primary particles is 50 nm to 2 μm. The secondary particles include: The first type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm. Based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N1, 2% ≤ N1 < 10%. The second type of secondary particles, the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm. Based on the total number of secondary particles, the proportion of the number of the second type of secondary particles is N2, 70% ≤ N2 < 85%. The third type of secondary particles, the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm. Based on the total number of secondary particles, the proportion of the number of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

2. The lithium ion secondary battery according to claim 1, characterized in that: One or two or three of the first type of secondary particles, the second type of secondary particles, and the third type of secondary particles are circular secondary particles. The circular secondary particles are those in the scanning electron microscope image, and the ratio of the longest diameter to the shortest diameter of the secondary particles is d1 / d2, 1 ≤ d1 / d2 ≤ 1.

2.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The ratio of the number of the second type of secondary particles to the number of the first type of secondary particles is 7 to 42.

5.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The average particle size of the primary particles is 100 nm to 500 nm.

5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The compaction density of the positive electrode active material under a pressure of 5T is 3.35 g / cm 3 ~3.6g / cm 3 .

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The specific surface area of ​​the positive electrode active material is 0.35 m 2 / g~0.75m 2 / g.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The weight is 1.4×10 -4 g / mm 2 ~2.3×10 -4 g / mm 2 The compaction density of the positive electrode sheet at 0.7% extension is 3.35 g / cm 3 ~3.7g / cm 3 .

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that: The positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O n material; 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤n≤2.2, M1 includes a combination of one or more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, and Ti.

9. A method for preparing a lithium ion secondary battery, characterized in that: It includes: Providing a slurry containing a positive electrode active material, coating the slurry containing the positive electrode active material on a positive electrode current collector to form a positive electrode plate. The positive electrode active material includes lithium nickel cobalt manganese oxide. The molar content of nickel element in all transition metal elements is greater than or equal to 0.

85. The positive electrode active material includes secondary particles, and the secondary particles include primary particles. The average particle size of the primary particles is 50 nm to 2 μm. The secondary particles include the first type of secondary particles, the second type of secondary particles and the third type of secondary particles. The volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm. Based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N1, 2% ≤ N1 < 10%. The volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm. Based on the total number of secondary particles, the proportion of the number of the second type of secondary particles is N2, 70% ≤ N2 < 85%. The volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm. Based on the total number of secondary particles, the proportion of the number of the third type of secondary particles is N3, 5% ≤ N3 < 28%. Setting a separator between the positive electrode plate and the negative electrode plate to form a lithium ion secondary battery.

10. The method for preparing a lithium-ion secondary battery according to claim 9, characterized in that: The preparation method of the positive electrode active material includes: Providing a solution containing a nickel source, a cobalt source and a manganese source, wherein the molar ratio of the nickel source, the cobalt source and the manganese source is x:y:(1-xy), x≥0.85; Adding a complexing agent with a concentration of 0.2 mol / L to 3.5 mol / L and a precipitating agent with a concentration of 0.3 mol / L to 0.5 mol / L to the solution containing the nickel source, the cobalt source and the manganese source, controlling the pH in the range of 12.1 to 13 under an inert atmosphere, reacting at 50 to 70° C. for 4 to 7 hours to form a first intermediate product; The pH of the first intermediate product is adjusted to 10.5-11, and the reaction is carried out for 13-17 hours to obtain a second intermediate product; The pH of the second intermediate product is adjusted to 10 to 10.4, and the reaction is carried out for 55 to 80 hours to obtain nickel-cobalt-manganese hydroxide, wherein the volume average particle size DV50 of the nickel-cobalt-manganese hydroxide is 8.5 μm to 12 μm; The nickel-cobalt-manganese hydroxide is mixed with a lithium salt and sintered to obtain a lithium-nickel-cobalt-manganese oxide positive electrode material.

11. The method for preparing a lithium ion secondary battery according to claim 10, characterized in that: The nickel-cobalt-manganese hydroxide is mixed with a lithium salt and sintered to obtain a lithium-nickel-cobalt-manganese oxide positive electrode material, comprising: The nickel-cobalt-manganese hydroxide is mixed with a lithium salt and subjected to a first sintering to obtain a first product; The first product is mixed with a first coating source, and subjected to a second sintering to obtain a second product, wherein the temperature of the second sintering is lower than the temperature of the first sintering.

12. The method for preparing a lithium ion secondary battery according to claim 11, characterized in that: The first sintering temperature is 725° C. to 780° C., and the first sintering time is 7 h to 14 h; or / and, The temperature of the second sintering is 400° C. to 615° C., and the time of the second sintering is 5 h to 11 h.

13. The method for preparing a lithium ion secondary battery according to claim 11 or 12, characterized in that: The nickel-cobalt-manganese hydroxide is mixed with a lithium salt and subjected to a first sintering to obtain a first product, comprising: The nickel-cobalt-manganese hydroxide, lithium salt and doping source are mixed and subjected to a first sintering to obtain a first product, wherein the doping source includes one or more of a Mg source, a Na source, a Zr source, a Y source, an Al source, a Ca source, a W source, a Nb source, a Ta source, a Sr source or a Ti source.

14. The method for preparing a lithium ion secondary battery according to any one of claims 11 to 13, characterized in that: The first coating source includes one or more of a Co source, an Al source, a F source, and a Ti source.

15. The method for preparing a lithium ion secondary battery according to any one of claims 11 to 14, wherein after mixing the first product with the first coating source and performing a second sintering to obtain the second product, the method further comprises: The second product is mixed with the second coating source, and after a third sintering, a third product is obtained, wherein the third product is a lithium nickel cobalt manganese oxide positive electrode material. 16 . The method for preparing a lithium-ion secondary battery according to claim 15 , wherein the temperature of the third sintering is 250° C. to 348° C., and the time of the third sintering is 5 h to 12 h; and the second coating source comprises the first one or more of a B source, an Al source, and a Y source.

17. A positive electrode active material, characterized in that: The positive electrode active material comprises lithium nickel cobalt manganese oxide, wherein the molar content of nickel in all transition metal elements is greater than or equal to 0.85; the positive electrode active material comprises secondary particles, the secondary particles comprise primary particles, and the average particle size of the primary particles is 50 nm to 2 μm; The secondary particles include: The first type of secondary particles, the volume particle size distribution of the first type of secondary particles is d11, 3 μm < d11 ≤ 7.5 μm; based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N1, 2% ≤ N1 < 10%; The second type of secondary particles, the volume particle size distribution of the second type of secondary particles is d12, 7.5 μm < d12 ≤ 11 μm; based on the total number of secondary particles, the proportion of the number of the first type of secondary particles is N2, 70% ≤ N2 < 85% The third type of secondary particles, the volume particle size distribution of the third type of secondary particles is d13, 11 μm < d13 ≤ 15 μm; based on the total number of secondary particles, the proportion of the number of the third type of secondary particles is N3, 5% ≤ N3 < 28%.

18. The positive electrode active material according to claim 17, characterized in that One or two or three of the first type of secondary particles, the second type of secondary particles, and the third type of secondary particles are circular secondary particles. The circular secondary particles are those in the scanning electron microscope image, and the ratio of the volume particle size distribution to the shortest diameter of the secondary particles is d1 / d2, 1 ≤ d1 / d2 ≤ 1.

2.

19. The positive electrode active material according to claim 17 or 18, characterized in that: The positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 (1-b-c-d) O n material; 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤n≤2.2, M1 includes a combination of one or more of Mg, Na, Zr, Y, Al, Ca, W, Nb, Ta, Sr, and Ti.

20. A method for preparing a positive electrode active material, characterized in that: Including: Providing a solution containing a nickel source, a cobalt source, and a manganese source, wherein the molar ratio of the nickel source, the cobalt source, and the manganese source is x:y:(1 - x - y), x ≥ 0.85; Adding a complexing agent with a concentration of 0.2 mol / L to 3.5 mol / L and a precipitating agent with a concentration of 0.3 mol / L to 0.5 mol / L into the solution containing the nickel source, the cobalt source, and the manganese source. Under an inert atmosphere, controlling the pH range to be 12.1 to 13, and reacting at 50 to 70 °C for 4 h to 7 h to form a first intermediate product; Adjusting the pH of the first intermediate product to 10.5 to 11 and reacting for 13 h to 17 h to obtain a second intermediate product; Adjusting the pH of the second intermediate product to 10 to 10.4 and reacting for 55 h to 80 h to obtain nickel cobalt manganese hydroxide, and the volume average particle size DV50 of the nickel cobalt manganese hydroxide is 8.5 μm to 12 μm; Mix the nickel cobalt manganese hydroxide with a lithium salt and sinter to obtain a lithium nickel cobalt manganese oxide cathode material. The cathode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.

85. The cathode active material includes secondary particles, and the secondary particles include primary particles, and the average particle size of the primary particles is 50 nm to 2 μm. The secondary particles include a first type of secondary particle, a second type of secondary particle, and a third type of secondary particle. The volume particle size distribution of the first type of secondary particle is d11, where 3 μm < d11 ≤ 7.5 μm. Based on the total number of secondary particles, the proportion of the number of the first type of secondary particle is N1, where 2% ≤ N1 < 10%. The volume particle size distribution of the second type of secondary particle is d12, where 7.5 μm < d12 ≤ 11 μm. Based on the total number of secondary particles, the proportion of the number of the second type of secondary particle is N2, where 70% ≤ N2 < 85%. The volume particle size distribution of the third type of secondary particle is d13, where 11 μm < d13 ≤ 15 μm. Based on the total number of secondary particles, the proportion of the number of the third type of secondary particle is N3, where 5% ≤ N3 < 28%.

21. The method for preparing a positive electrode active material according to claim 20, characterized in that: The step of mixing the nickel cobalt manganese hydroxide with a lithium salt and sintering to obtain a lithium nickel cobalt manganese oxide cathode material includes: Mix the nickel cobalt manganese hydroxide with a lithium salt and perform a first sintering to obtain a first product. The temperature of the first sintering is 725°C to 780°C, and the time of the first sintering is 7 h to 14 h. Mix the first product with a first coating source and perform a second sintering to obtain a second product. The temperature of the second sintering is 400°C to 615°C, and the time of the second sintering is 5 h to 11 h. The first coating source includes one or more of Co source, Al source, F source, and Ti source. Mix the second product with the second coating source and perform a third sintering to obtain a third product, which is a lithium nickel cobalt manganese oxide cathode material. The temperature of the third sintering is 250°C to 348°C, and the time of the third sintering is 5 h to 12 h. The second coating source includes one or more of B source, Al source, and Y source.

22. The method for preparing the positive electrode active material according to claim 20 or 21, characterized in that: The step of mixing the nickel cobalt manganese hydroxide with a lithium salt and sintering to obtain a lithium nickel cobalt manganese oxide cathode material includes: Mix the nickel cobalt manganese hydroxide, lithium salt, and doping source, and perform a first sintering to obtain a first product. The doping source includes one or more of Mg source, Na source, Zr source, Y source, Al source, Ca source, W source, Nb source, Ta source, Sr source, or Ti source.

23. An electrical equipment, characterized in that: Including the lithium ion secondary battery according to any one of claims 1-8, and / or the lithium ion secondary battery prepared by the preparation method according to any one of claims 9-16, and / or the cathode active material according to any one of claims 17-19, and / or the cathode active material prepared by the preparation method of the cathode active material according to any one of claims 20-22.

Citation Information

Patent Citations

  • Pressure-resistant positive electrode active material and electrochemical energy storage device

    CN111384371A

  • Positive electrode material, and electrochemical device and electronic device comprising same

    CN113169322A

  • Preparation of concentration gradient magnesium-doped lithium-rich manganese-based oxide positive electrode material and lithium battery application of concentration gradient magnesium-doped lithium-rich manganese-based oxide positive electrode material

    CN113299902A

  • Nonaqueous electrolyte secondary battery

    CN114467199A

  • Ternary positive electrode material, method for manufacturing same, and secondary battery using same

    CN115832268A

Cited By

  • Positive electrode active material, positive electrode sheet, and electrochemical device

    CN121123247A